(untitled) (Mongolian Journal of Agricultural Sciences, 2024)
To protect the ecosystem of Lake Khövsgöl and eliminate hazardous waste, the Government of Mongolia undertook the recovery of the sunken Sükhbaatar ship. This study presents the engineering design, analysis, and application of rigger equipment used in the retrieval process, with a particular focus on the calculation, selection, and deployment of steel wire ropes to generate the required pulling force. The Sükhbaatar ship, constructed in the former Soviet Union in 1956, measured 43.3 meters in length, 8.4 meters in width, and 11.4 meters in height (including the antenna), with a hull height of 5.7 meters, a total weight of 309 tons, and a cargo capacity of 400 tons. After sinking in 1985, the vessel was successfully retrieved during a 37-day operation conducted from October 1 to November 7, 2021. The recovery was executed using a combination of pulling and lifting forces generated by specialized rigging systems, including winches, pulleys, and steel wire ropes, under challenging environmental and operational conditions.